MIMO radar with spatial-frequency diversity for improved detection performance - Shanbhag, Kiran V; Deb, Debasish; Kulkarni, Muralidhar (2010 IEEE International Conference on Communication Control and Computing Technologies, 2010)
The Multiple Input Multiple Output (MIMO) radar concept exploits the independence between signals at the array elements unlike beamforming which presumes a high correlation between signals either transmitted or received by an array. Radar Cross Section (RCS) of a complex target varies with both transmitted frequency and target geometry. By widely separating transmit and receive antennas, MIMO radar systems observe a target simultaneously from different aspects resulting in spatial diversity, thus improving the detection performance. Also by utilizing different frequencies, independent RCS of the target can be observed, thus resulting in frequency diversity. In this paper, the spatial and the frequency diversities are studied together to bring out the combined benefits. The system proposed will not only have several antennas appropriately spaced but also several operating frequencies appropriately spaced, providing a better detection performance than conventional MIMO radar systems for the same transmission power. The simulation results exhibit a better detection performance of the proposed system as compared to MIMO radar systems with only spatial diversity.